Corporeización en la toponimia quechua - Manallay Moreno, Pedro Luis (2022)
This article analyzes the embodiment thesis through toponymic data of two dialects of the Quechua language: Llata (Huánuco) and Huaccana (Apurímac). We will show that the Quechua toponymic system supports the aforementioned thesis, since experiences are important to generate conceptualizations about geographical points. Likewise, will we argue that, in toponymic production, the process of ontological prominence (Schmid, 2007) is necessary to elaborate the names of places. In sum, we will establish a line between the cultural semantic mechanisms and the universal semantic mechanisms found in Quechua place names.